Penerapan Manajemen Konflik dalam Mempertahankan Kualitas Kinerja Karyawan pada PT. Boncafe Lestari - Nisia Yuanida; Nahdya Alfaina Karem; Andriani Andriani (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2024)
This research aims to analyze the application of conflict management in maintaining the quality of employee performance at PT. Boncafe Lestari. The method used in this research is a qualitative approach by collecting data through interviews and direct observation in the work environment. The research results show that effective conflict management can improve cooperative relationships between employees and reduce the negative impact of conflicts that occur. In addition, implementing clear policies and interpersonal communication training also contributes to creating a harmonious work environment. It is hoped that this research can contribute to companies in managing conflict and maintaining the quality of employee performance.